Monoatomic POD (peroxidase) imitating enzyme nano material as well as preparation method and food safety detection application thereof
By anchoring precious metal Os on the defective metal oxide Cu-Ov, forming single-atom POD enzyme nanomaterials, the problem of expensive and low efficiency of nitrite detection equipment in the prior art is solved, and efficient and accurate foods are achieved Safety inspection, providing cheap colorimetric biosensors and food quick inspection tools.
Patent Information
- Application Number
- CN202411266263.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The existing food safety detection technology has problems such as expensive equipment, long time consumption, complex operation, high cost, and low conversion efficiency of nanoenzyme metal active center energy substrates for nitrite detection, making it difficult to meet the entire chain of food production, processing and sales. Real-time monitoring of requirements.
A single-atom POD enzyme nanomaterial was developed to form POD enzyme nanomaterials by anchoring precious metal Os on the defective metal oxide Cu-Ov, and nitrite detection was performed using its high catalytic activity and selectivity. The material is prepared by hydrothermal reaction, with Os anchored on Cu-Ov in a single atom form to form OsCu-Ov nanomaterials for efficient colorimetric detection instead of natural enzymes.
It realizes efficient and accurate detection of nitrites, has a low detection limit, is suitable for food safety monitoring, provides cheap and sensitive colorimetric biosensors, and maintains efficient work under different conditions, and is suitable as a food quick inspection tool.
Smart Images

Figure CN119114100A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical fields of nano materials, analysis and detection, and food safety, and specifically relates to a single-atom POD enzyme-mimicking nano material, a preparation method thereof, and food safety detection application. Background Art
[0002] Food safety has become a major challenge faced by the whole world. It not only causes great harm to human health, but also seriously restricts import and export trade and industrial development. Nitrite is usually used as a preservative and colorant in food processing and is widely present in daily life. Excessive intake of food additives such as nitrite can cause a series of adverse reactions, such as methemoglobinemia, headache, dizziness, rapid heartbeat, nausea, and in severe cases, poisoning and death. Due to the potential carcinogenicity of nitrite, the World Health Organization (WHO) has listed it as a highly toxic substance. The Food and Agriculture Organization of the United Nations (FAO) and WHO set the maximum limit of nitrite in drinking water at 3.0 mg / L and the maximum daily intake of nitrite in food at 0.06 mg / kg. China's national food safety standard (GB 2762-2024) limits the maximum content of nitrite in milk powder and formula milk powder to 2.0 mg / kg, bottled water to 0.1 mg / L, the maximum amount added to meat products to 0.5 g / kg, and the maximum residual amount does not exceed 30 mg / kg. Therefore, the development of efficient and accurate nitrite detection technology is crucial to ensure food safety. Chromatographic methods such as gas chromatography, high-performance liquid chromatography, gas chromatography-mass spectrometry and high-performance liquid chromatography-mass spectrometry, and electrochemical methods are the most commonly used detection technologies in current food safety monitoring. Although it has the advantages of high sensitivity and good accuracy, it also has disadvantages such as expensive equipment, long time consumption, relatively complex operation, and high professional requirements for technical personnel. It cannot meet the needs of real-time and effective monitoring of the entire chain of food production, processing, circulation and sales. Therefore, the development of simple, accurate and economical on-site rapid detection technology has become a research hotspot.
[0003] Natural enzymes (such as peroxidase (POD), oxidase (OXD), catalase (CAT), superoxide dismutase (SOD), etc.) have been proven to have advantages such as high catalytic activity and strong substrate specificity. As core recognition materials or markers, they play an important role in common rapid detection technologies such as enzyme inhibition and immunoassay. However, due to their own limitations, such as poor stability, easy inactivation, high cost, and difficulty in preparation and purification, they are difficult to be widely used in rapid food safety detection technology, which limits their application and promotion.
[0004] With the continuous advancement of nanotechnology, researchers have gradually developed nanozymes that can simulate the catalytic activity of natural enzymes. These nanozyme preparations can not only simulate the catalytic process of natural enzymes such as OXD, POD and laccase, and regulate the activity of ROS production, but also have the advantages of high designability, versatility, stability, etc., and are expected to be used as efficient and accurate new enzyme-mimicking catalysts in the field of food safety detection technology. Biomimetic enzyme preparations represented by metal oxides (Fe3O4, CeO2, MoO3, Co3O4, MnO2, etc.), metal hydroxides (Cu(OH)2), metal nanoparticles (Ag and Au nanoparticles, Pd@Pt nanodendrites, etc.), carbon-based single-atom materials (Fe, Co, Zn-NC, etc.), etc., although they show certain food safety detection activity, they still face the following problems in food safety detection research: the energy substrate conversion efficiency of the metal active center of the nanozyme is low, the ROS production activity is insufficient, and large doses are often required to achieve efficient and rapid detection effects. However, high concentrations of ROS-producing materials also increase equipment costs, which greatly limits their application prospects in food safety detection. Therefore, designing a sensor with high catalytic activity, high selectivity and stability for nitrite content detection is the core and challenge of this project. Related research is of great significance to food safety monitoring. Summary of the invention
[0005] In view of the above defects, the present invention provides a novel enzyme-mimicking nanosensor, wherein the enzyme-mimicking nanomaterial comprises a noble metal Os and a defective metal oxide (named Cu-O v ), that is, anchoring the precious metal in the Cu-O v A peroxidase (POD) enzyme-mimicking nanomaterial is formed on the precursor; the enzyme-mimicking nanomaterial has POD activity and can therefore be used to accurately detect the content of substances such as nitrite (for example, in food safety testing).
[0006] The technical solution of the present invention:
[0007] The first technical problem to be solved by the present invention is to provide a single-atom POD enzyme-mimicking nanomaterial, which comprises a noble metal Os and a defective metal oxide, wherein the defective metal oxide is an oxide of metal Cu, and the Os is anchored on the defective metal oxide in the form of a single atom.
[0008] Furthermore, the defective metal oxide is an oxygen vacancy defective metal oxide.
[0009] Furthermore, the particle size of the single-atom POD enzyme-mimicking nanomaterial is 2-20 nm.
[0010] The second technical problem to be solved by the present invention is to provide a method for preparing the single-atom POD enzyme-mimicking nanomaterial described herein, which comprises the following steps:
[0011] (1) A copper salt and an amine compound are hydrothermally reacted in water, and the resulting precipitate is washed and dried to obtain a defective metal oxide.
[0012] (2) The defective metal oxide obtained in step (1) and the Os salt are mixed in water and stirred so that Os is anchored on the defective metal oxide in the form of a single atom. The obtained precipitate is washed and dried to obtain the single-atom POD enzyme-mimicking nanomaterial.
[0013] Furthermore, the copper salt includes CuCl2·xH2O.
[0014] Furthermore, the amine compound includes at least one of hexamethylenetetramine, urea, ammonium chloride and ammonium nitrate.
[0015] Furthermore, the mass ratio of the copper salt to the amine compound is 1:5-15.
[0016] Furthermore, the hydrothermal reaction is carried out at 60-150° C. for 1-12 hours.
[0017] Furthermore, the Os salt includes OsCl3·xH2O.
[0018] Furthermore, the mass ratio of the defective metal oxide to the Os salt is 50:1-25, preferably 5:2 to 10:1.
[0019] Further, the stirring comprises stirring at 20-100° C. for 5-48 hours.
[0020] The third technical problem to be solved by the present invention is to provide a use of the single-atom POD enzyme-mimicking nanomaterial described herein or the single-atom POD enzyme-mimicking nanomaterial prepared by the method described herein in preparing a detection reagent having POD activity.
[0021] The fourth technical problem to be solved by the present invention is to provide the use of the single-atom POD enzyme-mimicking nanomaterial described herein or the single-atom POD enzyme-mimicking nanomaterial prepared by the method described herein in the colorimetric detection of hydrogen peroxide or nitrite (for example, in food safety testing).
[0022] The fifth technical problem to be solved by the present invention is to provide a sensor for detecting hydrogen peroxide or nitrite (for example, in food safety testing), wherein the sensor comprises the single-atom POD enzyme-mimicking nanomaterial described herein or the single-atom POD enzyme-mimicking nanomaterial prepared by the method described herein.
[0023] Beneficial effects of the present invention:
[0024] The present invention anchors the precious metal Os uniformly and stably in the Cu-O v A new type of enzyme-mimicking nanomaterial (named OsCu-O v ), which can be used as a POD mimetic nanoreactor to replace natural enzymes for efficient and selective colorimetric detection of multiple biomarkers. Due to the unique enzyme properties of metal-O coordination, oxygen vacancies and noble metals present in the obtained enzyme-mimicking nanomaterials, the enzyme-mimicking nanomaterials show excellent and unique POD mimetic activity, and thus show excellent POD detection activity and good substrate selectivity.
[0025] The POD detection activity of the enzyme-mimicking nanomaterial obtained by the present invention. TMB, as a new type of chromogenic substrate, has been widely used in biochemical detection research. The chromogenic reaction of TMB oxidation is based on its core part: benzidine, which contains two easily oxidizable amino groups and can be oxidized into a blue product through an electronic pathway. In the presence of H2O2, POD can catalyze the oxidation of TMB (colorless) to form blue oxTMB with a characteristic absorption peak of 652nm. When nitrite is introduced, the generated blue oxTMB species will react specifically with nitrite to produce diazotized TMB, causing the color to change from blue to green and finally to yellow, which makes it possible to accurately detect nitrite.
[0026] In addition, the colorimetric test of the system shows that the enzyme-mimicking nanomaterial nanoreactor obtained by the present invention shows high diagnostic activity and substrate selectivity for food additive nitrite, and its detection limit is very low and the detection range is wide: 1.48mM for H2O2 in the range of 0-1350μM, and 2.23μM for nitrite in the range of 0.2-120μM. v The good stability of the structure also enables the nanoreactor to work efficiently under harsh conditions (such as different temperatures and different acidic conditions).
[0027] It can be seen that the present invention not only provides a highly sensitive and inexpensive colorimetric biosensor for food safety, but also will provide a new approach for engineering customizable enzyme-mimicking nanoreactors as a powerful tool for rapid food testing. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is the OsCu-O in Example 1 of the present invention v Schematic diagram of the synthesis.
[0029] Figure 2 is the Cu-O in Example 1 of the present invention v and OsCu-O v PXRD pattern of .
[0030] Figure 3 The SEM images of the materials obtained in Example 1 of the present invention are as follows: (a) Cu-O v SEM image of OsCu-O v SEM image of .
[0031] Figure 4 OsCu-O obtained in Example 1 of the present invention v HRTEM image of .
[0032] Figure 5 OsCu-O obtained in Example 1 of the present invention v Spherical aberration image.
[0033] Figure 6 The XPS scanning spectra of the material obtained in Example 1: (a) full spectrum; (b) high-resolution XPS C 1s; (c) high-resolution XPS O 1s; (d) high-resolution XPS Cu 2p; (e) high-resolution XPS Cl 1s; (f) high-resolution XPS Os4f.
[0034] Figure 7 OsCu-O obtained in Example 1 of the present invention v XAS image.
[0035] Figure 8 The results of the POD and OXD enzymatic activities of the materials obtained in Example 1 of the present invention were evaluated and compared using the TMB colorimetric method: (a) POD enzymatic activity; (b) Michaelis-Menten curve and double reciprocal curve when H2O2 was used as a substrate; (c) kinetic parameters when H2O2 was used as a substrate.
[0036] Fig. 9 The POD activity stability results of the materials obtained in Example 1 are as follows: (a) OsCu-O v POD activity at different temperatures and pH values; (b) OsCu-O v Solution stability during POD activity testing;
[0037] Fig.10 The product detection results of the POD catalytic process of the material obtained in Example 1: (a) free radical quenching process using TBA, BQ and NaN3 as quenchers during the POD simulation test; EPR results (b) ·OH, (c) ·O2 - and (d) 1 O2.
[0038] Fig.11The results of H2O2 detection of the materials obtained in Example 1: (a) At different concentrations of H2O2, OsCu-O v (a) POD-like activity absorbance spectrum; (b) H2O2 concentration dependence curve; (c) H2O2 linear correlation diagram.
[0039] Fig.12 The results of nitrite detection of the materials obtained in Example 1: (a) At different concentrations of nitrite, OsCu-O v (a) POD-like activity absorbance spectrum; (b) linear correlation diagram of nitrite.
[0040] Fig.13 The POD activity stability results of the materials obtained in Examples 1-5 are shown. DETAILED DESCRIPTION
[0041] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0042] Example 1: Single-atom POD enzyme-mimicking nanomaterial (named OsCu-O v )
[0043] Cu-O v Precursor: 10 mL of deionized water containing 340.9 mg of CuCl2·xH2O was mixed with 15 mL of deionized water containing 3.154 g of HMT (hexamethylenetetramine, urotropine), and the mixture was shaken and further hydrothermally treated in an autoclave at 95°C for 5 h; the precipitate was then washed with deionized water and dried under vacuum.
[0044] Nanosensor Material OsCu-O v Synthesis: 50 mg Cu-O v The mixture was dispersed in a flask with 10 mL of deionized water and subjected to continuous ultrasonic treatment for 10 min. Then, 0.5 mL of OsCl3·xH2O aqueous solution (concentration of 10 mg mL -1 ) was poured into the above solution; stirred at room temperature for 24 h, the precipitate was collected and washed with H2O solution at least 3 times, and then dried under vacuum at 60 ° C overnight to obtain OsCu-O v .
[0045] Example 2: OsCu-O v Structural characterization
[0046] Cu-O synthesized by hydrothermal method v, with Cu precursor and hexamethylenetetramine ligand; in addition, based on Os-O coordination, the Os catalytic sites simulating POD activity can be uniformly anchored on the Cu-O by hydrothermal synthesis and impregnation methods. v On the support, OsCu-O v The synthesis diagram of Figure 1 shown.
[0047] X-ray diffraction (XRD) patterns show that after anchoring the Os site, the Cu-O v The crystal structure has not changed significantly (such as Figure 2 Scanning electron microscope (SEM) images show that Cu-O v and OsCu-O v Shows a typical spherical shape with a diameter of about 30 nm (e.g. Figure 3 High-resolution transmission electron microscopy (HR-TEM) images show that the lattice fringe spacings of 0.2614, 0.2763, and 0.3165 nm are consistent with the Cu-O v The crystal planes (0 2 2)(1 2 1) and (0 2 1) are consistent (such as Figure 4 High-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) and energy dispersive spectroscopy (EDS) results further revealed that Os atoms are uniformly dispersed in the Cu-O v On the precursor (such as Figure 5 shown).
[0048] The present invention further performs X-ray photoelectron spectroscopy (XPS) testing to study the chemical composition and electronic state. The results are as follows Figure 6 And Table 1. XPS full spectrum and elemental analysis show that Os element is successfully doped into Cu-O v . With Cu-O v Compared with OsCu-O v The O1s of Os has an obvious peak shift, indicating the formation of Os-O coordination. The Os 4f spectrum shows that the oxidation state of Os atoms is mainly composed of Ir 3+ and Ir 4+ composition, indicating the formation of atomic-level Os coordinated by O. Os L3 edge synchrotron radiation x-ray absorption spectrum ( Figure 7 )Study the coordination structure of enzyme-mimicking materials. v The oxidation state of the white peak is closer to OsO2, and the valence state analysis shows that OsCu-O v The average valence of Os in OsCu-O is 4.2, which is slightly higher than that in OsO2. v There is only Os-O in the coordination structure, and there is no Os-Os coordination structure, indicating that Os exists in the form of a single atom.
[0049] Table 1 Element contents in the biocatalysts determined by XPS measurements.
[0050]
[0051] Example 3: OsCu-O v Performance Testing
[0052] Enzyme-like and colorimetric assays
[0053] After verifying that Cu-O v and OsCu-O v After studying the morphology and structure of the product, the present invention further studies its enzyme-mimicking activity and food additive content detection performance.
[0054] First, the activities of POD mimetics were evaluated and compared using a typical 3,3′,5,5′-tetramethylbenzidine (TMB) colorimetric assay. Figure 8 As shown in a, OsCu-O v It showed very efficient TMB oxidation activity with the highest characteristic absorption peak at 652 nm, while Cu-O v It showed very poor POD mimetic activity. m ), maximum reaction rate (V max ) and turnover number (TON) further revealed the POD-like activity. The results are shown in Table 2 and Figure 8 As shown in bc, OsCu-O v With H2O2 as substrate, the double reciprocal plot of Michaelis–Menten kinetics showed a good linear fitting relationship; the results of kinetic parameters showed that OsCu-O v The POD-mimetic activity has fast reaction kinetics.
[0055] Table 2. OsCu-O v Kinetic parameters with H2O2 as substrate
[0056] <![CDATA[E0(μM)]]> <![CDATA[V max (μM s -1 )]]> <![CDATA[K m (mM)]]> <![CDATA[TON(s -1 )]]> H2O2 5.44 1.41 18.5 259.9
[0057] At the same time, the nanoreactor obtained by the present invention still has high catalytic activity under different reaction conditions, for example, at different temperatures and in different pH ranges ( Fig. 9 a). At the same time, in order to verify the v The long-term structural stability of OsCu-O v The samples were placed in NaOAc-HOAc buffer (pH 4.5) for different time periods, and the POD mimetic activity did not weaken, indicating that it has good POD mimetic stability ( Fig. 9 b).
[0058] Then, free radical quenching experiments and EPR analysis were applied to identify the products in the POD simulation process with H2O2 as substrate. The addition of potassium p-tert-butoxide (TBA, a free radical quencher of ·OH), benzoquinone (BQ, a ·O2 - free radical quencher) and sodium azide (NaN3, a 1 After the addition of oxTMB (a free radical quencher of O2), the intensity value of oxTMB at 652nm decreased, confirming that the main products generated were ·OH, ·O2 - and 1 O2( Fig.10 a). Then, EPR further confirmed that ·OH, ·O2 - and 1 O2 generation ( Fig.10 bd). In summary, the present invention has proved that ·OH, ·O2 - and 1 O2 is the main product in the POD simulation process.
[0059] Colorimetric detection of H2O2
[0060] Since OsCu-O v The excellent POD mimetic properties indicate that the obtained nanomaterials can be used for quantitative detection by colorimetrically evaluating H2O2 levels. Fig.11 As shown in a, the characteristic absorption peak at 652nm gradually increases with the increase of H2O2 concentration. The ratio between absorbance and H2O2 concentration (0-1350μM) is linearly correlated ( Fig.11 b). At the same time, after calculation, the LOD of H2O2 detection is 1.48mM, indicating that the OsCu-O v It showed high detection activity for H2O2.
[0061] Colorimetric detection of nitrite
[0062] like Fig.12 As shown in a, the characteristic absorption peak at 652nm gradually decreases with the increase of nitrite concentration, and the characteristic absorption peak at 445nm gradually increases with the increase of nitrite concentration. 652 / A 445 The ratio between absorbance and nitrite concentration (0.2-120 μM) is linearly correlated ( Fig.12 b). At the same time, after calculation, the LOD of nitrite detection is 2.23 μM, indicating that the OsCu-O v Shows high detection activity for nitrite.
[0063] Example 4: Changing Cu-O vPreparation of OsCu-O v
[0064] Cu-O v Precursor: 10 mL of deionized water containing 340.9 mg of CuCl2·xH2O was mixed with 15 mL of deionized water containing 3.154 g of HMT (hexamethylenetetramine, urotropine), and the mixture was shaken and further hydrothermally treated in an autoclave at 95°C for 5 h; the precipitate was then washed with deionized water and dried under vacuum.
[0065] Nanosensor Material OsCu-O v Synthesis: 50 mg Cu-O v The mixture was dispersed in a flask with 10 mL of deionized water and subjected to continuous ultrasonic treatment for 10 min. Then 1 mL of OsCl3·xH2O aqueous solution (concentration 10 mg mL -1 ) was poured into the above solution; stirred at room temperature for 24 h, the precipitate was collected and washed with H2O solution at least 3 times, and then dried under vacuum at 60 ° C overnight to obtain OsCu-O v (Cu-O v :Os=5:1). The results showed that the obtained OsCu-O v (Cu-O v :Os=5:1) has good POD activity ( Fig.13 ).
[0066] Example 5: Changing Cu-O v Preparation of OsCu-O v
[0067] Cu-O v Precursor: 10 mL of deionized water containing 340.9 mg of CuCl2·xH2O was mixed with 15 mL of deionized water containing 3.154 g of HMT (hexamethylenetetramine, urotropine), and the mixture was shaken and further hydrothermally treated in an autoclave at 95°C for 5 h; the precipitate was then washed with deionized water and dried under vacuum.
[0068] Nanosensor Material OsCu-O v Synthesis: 50 mg Cu-O v The mixture was dispersed in a flask with 10 mL of deionized water and subjected to continuous ultrasonic treatment for 10 min. Then 2 mL of OsCl3·xH2O aqueous solution (concentration of 10 mg mL -1 ) was poured into the above solution; stirred at room temperature for 24 h, the precipitate was collected and washed with H2O solution at least 3 times, and then dried under vacuum at 60 ° C overnight to obtain OsCu-O v (Cu-Ov :Os=10:4). It was found that the obtained OsCu-O v (Cu-O v :Os=10:4) has good POD activity ( Fig.13 ).
[0069] Example 6: Changing Cu-O v Preparation of OsCu-O v
[0070] Cu-O v Precursor: 10 mL of deionized water containing 340.9 mg of CuCl2·xH2O was mixed with 15 mL of deionized water containing 3.154 g of HMT (hexamethylenetetramine, urotropine), and the mixture was shaken and further hydrothermally treated in an autoclave at 95°C for 5 h; the precipitate was then washed with deionized water and dried under vacuum.
[0071] Nanosensor Material OsCu-O v Synthesis: 50 mg Cu-O v The mixture was dispersed in a flask with 10 mL of deionized water and subjected to continuous ultrasonic treatment for 10 min. Then, 0.2 mL of OsCl3·xH2O aqueous solution (concentration of 10 mg mL -1 ) was poured into the above solution; stirred at room temperature for 24 h, the precipitate was collected and washed with H2O solution at least 3 times, and then dried under vacuum at 60 ° C overnight to obtain OsCu-O v (Cu-O v :Os=25:1). The results showed that the obtained OsCu-O v (Cu-O v :Os=25:1) has poor POD activity ( Fig.13 ).
[0072] Comparative Example 1: Anchoring the precious metal Ru to Cu-O v RuCu-O v POD activity
[0073] Cu-O v Precursor: 10 mL of deionized water containing 340.9 mg of CuCl2·xH2O was mixed with 15 mL of deionized water containing 3.154 g of HMT (hexamethylenetetramine, urotropine), and the mixture was shaken and further hydrothermally treated in an autoclave at 95°C for 5 h; the precipitate was then washed with deionized water and dried under vacuum.
[0074] Nanosensor Material RuCu-O v Synthesis: 50 mg Cu-O vThe mixture was dispersed in a flask with 10 mL of deionized water and subjected to continuous ultrasonic treatment for 10 min. Then 1 mL of RuCl3·xH2O aqueous solution (concentration 10 mg mL -1 ) was poured into the above solution; stirred at room temperature for 24 h, the precipitate was collected and washed with H2O solution at least 3 times, and then dried under vacuum at 60 ° C overnight to obtain RuCu-O v (Cu-O v :Ru=5:1). It was found that the obtained RuCu-O v (Cu-O v :Ru=5:1) has no POD activity ( Fig.13 ).
[0075] Comparative Example 2: Anchoring the transition metal Fe to Cu-O v FeCu-O v POD activity
[0076] Cu-O v Precursor: 10 mL of deionized water containing 340.9 mg of CuCl2·xH2O was mixed with 15 mL of deionized water containing 3.154 g of HMT (hexamethylenetetramine, urotropine), and the mixture was shaken and further hydrothermally treated in an autoclave at 95°C for 5 h; the precipitate was then washed with deionized water and dried under vacuum.
[0077] Nanosensor Material FeCu-O v Synthesis: 50 mg Cu-O v Dispersed in a flask with 10 mL of deionized water, the mixture was ultrasonically treated for 10 min; then 1 mL of FeCl3 aqueous solution (concentration 10 mg mL -1 ) was poured into the above solution; stirred at room temperature for 24 h, the precipitate was collected and washed with H2O solution at least 3 times, and then dried under vacuum at 60 ° C overnight to obtain FeCu-O v (Cu-O v :Fe=5:1). It was found that the obtained FeCu-O v (Cu-O v :Fe=5:1) with no POD activity ( Fig.13 ).
[0078] It should be noted that the preferred embodiments of the present invention are given in the specification of the present invention, but the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not intended to be additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all considered to be within the scope of the present invention specification; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.
Claims
1. A single-atom POD enzyme-mimicking nanomaterial, characterized in that: The single-atom POD enzyme-mimicking nanomaterial comprises a noble metal Os and a defective metal oxide, wherein the defective metal oxide is an oxide of metal Cu, and the Os is anchored on the defective metal oxide in the form of a single atom.
2. The single-atom POD enzyme-mimicking nanomaterial according to claim 1, characterized in that: The defective metal oxide is an oxygen vacancy defective metal oxide.
3. A method for preparing the single-atom POD enzyme-mimicking nanomaterial according to claim 1 or 2, characterized in that: The following steps are involved: (1) A copper salt and an amine compound are hydrothermally reacted in water, and the resulting precipitate is washed and dried to obtain a defective metal oxide. (2) The defective metal oxide obtained in step (1) and the Os salt are mixed in water and stirred so that Os is anchored on the defective metal oxide in the form of a single atom. The obtained precipitate is washed and dried to obtain the single-atom POD enzyme-mimicking nanomaterial.
4. The method according to claim 3, characterized in that The copper salt includes CuCl2·xH2O; The amine compound includes at least one of hexamethylenetetramine, urea, ammonium chloride and ammonium nitrate; The mass ratio of the copper salt to the amine compound is 1:5-15.
5. The method according to claim 3, characterized in that: The hydrothermal reaction conditions are 60-150° C. for 1-12 hours.
6. The method according to claim 3, characterized in that The Os salt includes OsCl3·xH2O; The mass ratio of defective metal oxide to Os salt is 50:1-25.
7. The method according to claim 3, characterized in that The stirring includes stirring at 20-100° C. for 5-48 hours.
8. Use of the single-atom POD enzyme-mimicking nanomaterial according to claim 1 or 2 or the single-atom POD enzyme-mimicking nanomaterial prepared by the method according to any one of claims 3 to 7 in preparing a detection reagent having POD activity.
9. Use of the single-atom POD enzyme-mimicking nanomaterial according to claim 1 or 2 or the single-atom POD enzyme-mimicking nanomaterial prepared by the method according to any one of claims 3 to 7 in the colorimetric detection of hydrogen peroxide or nitrite.
10. A sensor for detecting hydrogen peroxide or nitrite, characterized in that: The sensor comprises the single-atom POD enzyme-mimicking nanomaterial according to claim 1 or 2 or the single-atom POD enzyme-mimicking nanomaterial prepared by the method according to any one of claims 3-7.
Citation Information
Patent Citations
Monatomic noble metal loaded cerium oxide nano-enzyme, application and medicine
CN114558030A
Monatomic supported Os-WO2.72 electro-catalytic material as well as preparation method and application thereof
CN115404508A
Ruthenium monatomic catalyst with active oxygen scavenging effect and preparation of ruthenium monatomic catalyst
CN115920927A
Method for detecting nitrite in food based on Fe monatomic nano-enzyme
CN115931843A
Novel method of manufacture of metal nanoparticles and metal single-atom materials on various substrates and novel compositions
US20210252486A1
Cited By
Application of cell membrane coated oxygen vacancy Cu2 (OH) 3Cl loaded Os monatomic bionic enzyme preparation
CN120054548A
